Peningkatan Kapasitas Anggota Wanita Kelompok Tani Pade Girang Melalui Pelatihan Foto Produk Menggunakan Smartphone - Rifani Nur Sindy Setiawan; Ni Made Nike Zeamita Widiyanti; Eka Nurminda Dewi Mandalika; Farah Ainun Jamil; Sharfina Nabila (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
This activity aimed to improve the ability of the Pade Girang to produce attractive product photographs using smartphones for digital marketing purposes. The activity focused on processed banana products, which had limited market appeal due to poor visual presentation in social media promotion. The program was conducted from June to July 2025 using a participatory approach consisting of preparation, training, practice, and evaluation stages. Training materials included smartphone camera features, lighting techniques, product arrangement, background selection, shooting angles, and simple photo editing applications. The activity involved 15 participants and emphasized direct practice using participants’ own products. The results showed an improvement in participants’ understanding and technical skills in taking clearer, more attractive, and marketable product photographs. Participants became more capable of using natural lighting, arranging product composition, and selecting appropriate photo angles. In addition, the training encouraged participants to understand the importance of visual presentation in digital marketing. Several participants began using social media to promote their products after the training. Overall, the activity contributed to strengthening the marketing capacity of the farmer group and supporting wider market access for processed banana products.